Alpha and omega - Turtledove, Harry (Del Rey, 2019)
"What would happen if the ancient prophecy of the End of Days came true? It is certainly the last thing Eric Katz--a secular archeologist from Los Angeles--expects to discover during what should be a routine dig in Jerusalem. But perhaps higher forces have something else in mind. For when a sign presaging the rising of the Third Temple is located in America and a dirty bomb is detonated in downtown Tel Aviv, events conspire to place a team of archaeologists in the tunnels deep under the Temple Mount. And there, Eric is witness to a discovery of such monumental proportions that nothing will ever be the same again"--